Effect of incorporating sugar beet pulp in the finisher diet on performance of geese. (1st December 2014) - Arroyo, J.; Brachet, M.; Dubois, J. P.; Lavigne, F.; Molette, C.; Bannelier, C.; Fortun-Lamothe, L.
Abstract : The aim of this work was to study the effects of incorporating sugar beet pulp (SBP) into the diet on the development of the crop and performance of geese. A total of 480 1-day-old ganders were divided into three groups differing in the composition and mode of distribution of the diet offered from day 56 to 89. The following two diets were used: a standard diet (nitrogen-corrected apparent metabolizable energy, AMEn 11.44 MJ/kg; 160 g/kg CP) or a diet containing 10% of SBP (SBP diet; AMEn 11.47 MJ/kg; 160 g/kg CP). The swelling capacity (SC) hydration was higher for SBP than for the standard diet (3.62 v. 2.72 ml of H2 O/g of dry matter at 60 min; P <0.05). In the Control group, birds were fed with a controlled time of access to a standard diet. Other birds were fed the SBP diet with a controlled time of access (SBPt group) or a controlled quantity offered (SBPq). From day 90 to 104, 88 birds/group were overfed with a mixture containing mainly corn. Body traits including volume of the crop were measured at day 89. Fatty liver weight and commercial grading were measured at d 104. Feed intake from day 56 to 89 was higher in the Control group than in the SBPt group (8097 v. 7545 g; P <0.05), feed intake in the SBPq group being intermediate (7801 g); however, live weights (LW) of the birds were similar in the three groups measured at day 89 (5746 g; P >0.05). At day 89, the volume of the crop tended to be higher in the SBPt compared with the Control group (52.8 v. 48.8 ml/kg of LW; P =0.101). After overfeeding, feed intake (12 922 g), weight gain (2412 g), LW (8170 g), fatty liver weight (875 g) and commercial grading of the fatty liver were similar ( P >0.1) for all the three groups. Therefore, SBP could help adapt the digestive tract of waterfowl to high feed intake through an increase in the crop volume, but its method of use – that is, level of incorporation and mode of distribution – should continue to be investigated.